Preeclampsia Severa Es Un Factor De Riesgo Para Bajo Peso Al Nacer Y Mortalidad Perinatal De Los Productos De Gestantes Atendidas En El Hospital Belén De Trujillo, Durante El Periodo Junio 2008 – Junio 2013. - Castro Carranza, Katia Paola (2014)
Objective: Determine if severe Preeclampsia is a risk factor for low birth weight and perinatal mortality of the products of pregnant women treated in the Belen Hospital of Trujillo, during the period June 2008 - June 2013. Material and Methods: This research is a cohort study, retrospective, analytical, descriptive and comparative; the information was collected from medical records whose data were processed with the statistical package SPSS. 18.0 and analyzed with the Microsoft Office Excel program. The sample consisted of 401 medical histories that met the inclusion criteria of the study in each study group. Results: The 29.43 % of newborn of pregnant women with preeclampsia had low weight, an OR that indicates to us that are 6.85 more times risk that their products are of low birth weight. Also the 7.23 % died, OR tells us that the present 3.40 more times risk than their products submit perinatal mortality. Conclusions: Severe Preeclampsia is a risk factor for have low-birth-weight and increased risk of perinatal mortality.